Dynamic metabolic modeling of Streptomyces clavuligerus in complex medium highlights nutrient-dependent metabolic transitions associated with clavulanic acid biosynthesis - Leon F. Toro-Navarro; Laura Pinilla-Mendoza; Rigoberto Ríos-Estepa (PLoS ONE, 2026)
Background Streptomyces clavuligerus is the main industrial producer of clavulanic acid (CA), a potent β-lactamase inhibitor. However, the metabolic interplay linking amino acid utilization, nitrogen regulation, and CA biosynthesis remains poorly understood, particularly under complex medium conditions. Methods The genome-scale metabolic model iLT1021 was used to simulate the dynamic metabolism of S. clavuligerus cultivated in GLYCAS-5 medium. Dynamic flux balance analysis (dFBA) captured the transition from primary to secondary metabolism, while robustness analysis and amino acid network topology identified key metabolic control nodes. Results Integration of dFBA with experimental exometabolome data revealed a clear temporal pattern of amino acid consumption: glutamate, aspartate, and serine were rapidly depleted during exponential growth, whereas histidine and tryptophan were consumed later, coinciding with the onset of CA biosynthesis. Glutamate and glutamine emerged as central nitrogen carriers connecting the α-ketoglutarate and Arg–Orn pathways. Robustness analysis indicated that Arg and Orn enhanced CA fluxes, while Lys and Val had inhibitory effects. Under nitrogen limitation, accumulation of fructose-1,6-bisphosphate and reduced TCA activity reflected a redirection of carbon toward CA precursors. Conclusions This study provides the first genome-scale dynamic modeling of S. clavuligerus in a complex medium, demonstrating that amino acid availability and their temporal utilization pattern govern the metabolic switch from growth to CA biosynthesis. This integrative framework helps to interpret the metabolic behavior of S. clavuligerus growth in complex medium, offering valuable insights into nutrient regulation and secondary metabolism in filamentous bacteria.